Collaborative College Leadership - Maureen E Wilson; Dawn M Shinew; Brian M Campbell; Trinka E Messenheimer; Mary M Murray; Patrick D Pauken; Mark A Seals; Deborah G Wooldridge (Academic Chairpersons Conference Proceedings, 2019)
With the collaborative leadership style of a new dean, the Dean’s Executive Council (associate deans, school directors, chair) in the BGSU College of Education and Human Development transformed operations of the team and our work with college faculty. This has reenergized the college and garnered substantial faculty support and engagement.
Keywords: college leadership; collaboration; faculty engagement; strategic planning; leadership development